2015
DOI: 10.1371/journal.pone.0125349
|View full text |Cite
|
Sign up to set email alerts
|

Protection against T1DM-Induced Bone Loss by Zinc Supplementation: Biomechanical, Histomorphometric, and Molecular Analyses in STZ-Induced Diabetic Rats

Abstract: Several studies have established an association between diabetes and alterations in bone metabolism; however, the underlying mechanism is not well established. Although zinc is recognized as a potential preventive agent against diabetes-induced bone loss, there is no evidence demonstrating its effect in chronic diabetic conditions. This study evaluated the effects of zinc supplementation in a chronic (90 days) type 1 diabetes-induced bone-loss model. Male Wistar rats were distributed in three groups: control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 71 publications
4
33
0
1
Order By: Relevance
“…Skeletal alkaline phosphatase, another late marker of osteoblast activity, has been found to be low in diabetic children and adults, confirming poor osteoblast function [32, 33], as well as in most animal models of STZ-induced diabetes [10, 8, 27]. Expression of other key genes important for osteoblast bone metabolism and remodeling such as proteolytic members of the metalloproteinase family MMP2 (matrix metallopeptidase 2) and MMP9 were found to be increased in an animal model of STZ-induced diabetes [11], whereas in a model pairing STZ-induced diabetes with distraction osteogenesis, MMP9 and MMP13 were decreased [5]. Interestingly, in vitro studies have suggested that some of the hyperglycemic effects on the expression of genes encoding extracellular matrix proteins such as osteonectin, osteopontin, and collagen I can be attributed to osmotic changes [37-39].…”
Section: Effects Of Type 1 Diabetes On Osteoblastsmentioning
confidence: 94%
See 2 more Smart Citations
“…Skeletal alkaline phosphatase, another late marker of osteoblast activity, has been found to be low in diabetic children and adults, confirming poor osteoblast function [32, 33], as well as in most animal models of STZ-induced diabetes [10, 8, 27]. Expression of other key genes important for osteoblast bone metabolism and remodeling such as proteolytic members of the metalloproteinase family MMP2 (matrix metallopeptidase 2) and MMP9 were found to be increased in an animal model of STZ-induced diabetes [11], whereas in a model pairing STZ-induced diabetes with distraction osteogenesis, MMP9 and MMP13 were decreased [5]. Interestingly, in vitro studies have suggested that some of the hyperglycemic effects on the expression of genes encoding extracellular matrix proteins such as osteonectin, osteopontin, and collagen I can be attributed to osmotic changes [37-39].…”
Section: Effects Of Type 1 Diabetes On Osteoblastsmentioning
confidence: 94%
“…The Wnt/beta catenin pathway, which is essential for osteoblast differentiation and regulation of bone formation in differentiated osteoblasts, has also been shown to be down regulated in the bone of STZ-induced diabetic animals [10], partly due to increased expression of sclerostin and dickkopf-related protein 1 (Dkk1), two inhibitors of Wnt signaling. Interestingly, several studies describing altered expression of osteoblast regulating genes, such as Runx2, Dlx5, Osx, ALP, OC, Col1 and osteoclast genes, including osteoprotegerin (OPG), MMP9 and receptor activator of nuclear factor kappa-B ligand (RANKL) in diabetic bones, found that zinc supplementation can prevent these dysregulations and protect bones from diabetes induced damage [11, 12]. …”
Section: Effects Of Type 1 Diabetes On Osteoblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in recent years, the pathogenesis of T1DM has been examined intensely in research. STZ is widely used in the construction of the diabetes model experiment because it can specifically destruct pancreatic beta cells, which cause T1DM (Bortolin et al 2015, Carlos et al 2015, Lin & Sun 2015. In this experiment, the FBG levels of the normal control group were maintained within the normal range (4-6 mmol/L) throughout the feeding period.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of patients with T1DM have bone loss compared to healthy age-matched subjects (Muñoz-Torres et al, 1996;Kemink et al, 2000) markers of bone formation plasma insulin-like growth factor I (IGF-I), and a variety of bone-related changes are known to be influenced by hyperglycemia such as femoral neck geometry, microarchitecture and biomechanical markers of bone turnover (Starup-Linde, 2013;Bortolin et al, 2015;. However, the association between T1DM and bone mineral density (BMD) is controversial.…”
Section: Introductionmentioning
confidence: 99%